Effect of Different Planting Date and Variety in Some Morphological Characteristics of the Wheat Plant Triticum astivum L. - AL- Hadeathi, M. A. H.; AL- Hayani, E. H. H.; AL-Ani, S. S. H.; AL- Jubori, H. K. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Biological study was conducted in the botanical garden of the College of Education / Ibn Al-Haitham during the growing season 2006-2007 to determine the impact different date planting and variety in some morphological characteristics of the wheat plant Triticum astivum L.       Two varieties of Triticum aestivum L.: IPA99 and Abu-Ghraib , were cultivated in 4th , 25th of November and 9th of December .      The experiment was designed according to RCD in two replicates.       The results showed that cultivation of 4th November, gave rise to plants of high 74.66 cm, with the highest number of tillers which was 4.01 and the highest length of spike was 12.03 cm, while the plants planted on 9th   December gave the lowest high of plant 55.40 cm, the smallest number of total tillers 2.47 and shortest of spike 8.82 cm.       On the other hand the data showed that superiority of plant high of IPA99 on Abo-Graib item which reach 67.82 cm , while Abo-Graib item gave more tillers (3.40 cm) than IPA99 .